Segregação socioespacial e mobilidade urbana: uma análise a partir do caso da Jaubra, no distrito Brasilândia, São Paulo - SP - Brasil - Furtado, Dayana Brainer da Silva (2019)
Urban mobility in the city of São Paulo, defined as a criticism by many authors, has a more pronounced effect on the low socioeconomic strata, which, for the most part, live in segregated areas of the city where poor urban infrastructure prevails. In order to collaborate with mobility and accessibility, the new transport services provided by Transmission Technology Operators (OTTC's), based on the use of the Internet and Information and Communication Technologies [ICTs], arise. However, these services can also promote segregation insofar as their networks do not connect all points of the urban territory, thus contributing to the deepening of socio-spatial inequalities. The Brasilândia District, located in the north of São Paulo, is one of the examples related to this issue, since it is not served by the urban mobility services provided by the existing OTTCs. In the face of the obstacles presented, a local initiative was initiated by residents in response to the lack of mobility services through transport technologies. Thus the objective of this research was to study the social impact initiative developed in the Brasilândia District, called Jaubra, seeking to understand its origins, characteristics and potential for improving urban mobility in the region. For that, a methodological procedure of qualitative approach and descriptive character was chosen, starting from an exploratory study based on documentary analysis focusing on the urban mobility and social vulnerability conditions of the Brasilândia District and the description of the local Jaubra strategy. The results of this research show that Brasilândia remains with problems related to segregation and social vulnerability, irregular occupation and urban mobility. Given the context presented, it is concluded that experiences of local initiatives are rich and can become models for their replication in other areas that suffer from similar urban problems.